Composite positive electrode binder and preparation method thereof, positive plate and preparation method thereof, and all-solid-state battery
By using a composite positive electrode binder composed of the first polymer material and the second polymer material, the problems of high mechanical stress and serious layering of active materials during the positive electrode cycle of all solid lithium batteries are solved, and higher cycle stability and energy density are achieved.
Patent Information
- Application Number
- CN202411785688.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-06
AI Technical Summary
During the positive electrode cycle, existing all-solid-state lithium batteries have high mechanical stress and severe layering of active materials, resulting in poor stability and difficult to achieve high energy density.
A composite positive electrode binder composed of a first polymer material (such as poly(ethylene-methacrylate-glycidyl methacrylate)) and a second polymer material (such as hydrogenated nitrile rubber) is prepared by dissolving it in a non-polar solvent and centrifugingly drying to form a polar group-rich binder to prepare a high-performance positive electrode sheet.
The composite positive electrode binder has excellent adhesion and high ion and electron conductivity. It can alleviate micro cracking between the positive electrode and the electrolyte, broaden the lithium ion transmission channel, and significantly improve the cycle stability and energy density of the battery.
Smart Images

Figure CN119542424A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of all-solid-state battery material preparation, and specifically, to a composite positive electrode binder and a preparation method thereof, a positive electrode sheet and a preparation method thereof, and an all-solid-state battery. Background Art
[0002] Nowadays, electric vehicles generally use lithium-ion batteries. However, the use of lithium-ion batteries poses significant safety risks because they usually contain highly flammable liquid electrolytes that may cause fire or explosion under abnormal operating conditions. Therefore, all-solid-state lithium batteries using solid electrolytes are considered to be a promising development direction for current LIBs. Various solid electrolytes with high ionic conductivity and good interface contact with electrodes have been developed, which are usually polymers, inorganics, and composite electrolytes to improve the cycle performance of the battery. Among them, Li 10 GeP2S 12 Sulfide-based solid electrolytes such as Li6PS5X (X = Cl, Br, I) and Li2S-P2S5 have the highest ionic conductivity (about 10 –2 S cm –1 ), at room temperature, comparable to liquid electrolytes, sulfide all-solid-state lithium batteries are potential alternatives to traditional lithium-ion batteries, which can significantly improve battery energy density and battery safety. In addition, their ductility contributes to the large-scale production of batteries because it avoids high-temperature sintering and improves the processability of the battery's electrolyte and electrodes. However, the realization of high energy density in sulfide-based batteries is challenging due to the difficulty in producing sheet electrodes with high active mass loading. In order to avoid the delamination of active materials, conductive carbon and solid electrolyte in the positive electrode components and to alleviate the mechanical stress generated during the cycling process, the selection of suitable binders and positive electrode active materials is crucial to achieve the cycling performance of sulfide all-solid-state lithium batteries.
[0003] Therefore, there is an urgent need for a binder that can reduce the mechanical stress generated during the positive electrode cycling of solid-state batteries, avoid positive electrode stratification and maintain a high active mass loading of the positive electrode. Summary of the invention
[0004] In order to solve the technical problem of poor stability of all-solid-state batteries in the prior art, the present invention provides a composite positive electrode binder, a positive electrode sheet and a preparation method thereof, and an all-solid-state battery. The positive electrode sheet made with the composite positive electrode binder can produce an all-solid-state battery with better performance and stability.
[0005] In a first aspect, the present invention provides a composite positive electrode binder for an all-solid-state battery, wherein the composite positive electrode binder comprises a first polymer material and a second polymer material, wherein the molecular weight of the polymer material is 10 4 ~10 6 .
[0006] In one embodiment, the first polymer material includes at least one of poly(ethylene-methacrylate-glycidyl methacrylate), poly(ethylene-glycidyl methacrylate) and polyglycidyl methacrylate.
[0007] In one embodiment, the second polymer material includes at least one of hydrogenated nitrile rubber (HNBR), nitrile rubber (NBR), ethyl cellulose (EC), styrene butadiene rubber (SBR) and polyvinylidene fluoride (PVDF).
[0008] In one embodiment, the mass of the first polymer material is set to M, the mass of the second polymer material is set to N, and the M:N is (0.5-2):1;
[0009] A second aspect of the present invention provides a method for preparing a composite positive electrode binder, the method comprising the following steps:
[0010] S1, adding the first polymer material and the second polymer material into a non-polar solvent for dissolution;
[0011] S2, heating and stirring during dissolution;
[0012] S3, centrifugally drying to obtain a composite positive electrode binder.
[0013] In one embodiment, in the method for preparing the composite positive electrode binder, in step S1, the mass ratio of the first polymer material and the second polymer material to the solvent is 2% to 20%.
[0014] In one embodiment, in the method for preparing the composite positive electrode binder, the non-polar solvent in step S1 includes at least one of anisole, butyl butyrate, isobutyl isobutyrate, p-xylene and toluene.
[0015] The third aspect of the present invention provides a positive electrode sheet, comprising the first and second composite positive electrode binders, a conductive agent, a first solid electrolyte and a positive electrode active material.
[0016] A fourth aspect of the present invention provides a method for preparing a positive electrode sheet, the method comprising the following steps:
[0017] N1. Adding the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder into a solvent;
[0018] N2, stirring, repeating the mixing twice to form a uniform mixed slurry;
[0019] N3, coating the mixed slurry of step N2 on the positive electrode current collector;
[0020] N4, dry;
[0021] N5. After drying, roll pressing and slitting are performed to obtain the positive electrode sheet.
[0022] In one embodiment, in the method for preparing the positive electrode sheet, the mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder in step N1 is: (60-90): (8-38): (1-3): (1-3).
[0023] The fifth aspect of the present invention provides an all-solid-state battery, comprising the positive electrode sheet, the negative electrode sheet and the second solid electrolyte proposed in the third and fourth aspects.
[0024] Beneficial effects of the present invention:
[0025] The first polymer material has excellent adhesion, which can greatly alleviate the micro-cracks between the positive electrode and the electrolyte during the charge and discharge process and improve the battery stability; it also has higher ionic and electronic conductivity than traditional binders, which can broaden the lithium ion transmission channel and improve the battery cycle performance. In addition, the second polymer material and the first polymer material interact with each other, which can make the first polymer material better dispersed and dissolved in non-polar solvents; the obtained composite positive electrode binder is rich in polar groups, has excellent adhesion, and will not damage the sulfide electrolyte of the positive electrode material layer. Specifically, the electronic conductivity and ionic conductivity of the prepared positive electrode plate are higher than when using traditional binders. In addition, the capacity retention rate of the all-solid-state battery is higher after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:
[0027] Figure 1 This is the 0.1C charge and discharge curve of the battery in Example 1 of the present invention. Specific embodiments
[0028] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0030] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0031] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.
[0032] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.
[0033] Throughout the present invention, numerical values represent approximate measures or limits of ranges to cover minor deviations from given values as well as embodiments with about the values mentioned and embodiments with the exact values mentioned. Except for the working examples provided at the end of the detailed description, all numerical values of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood to be modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.
[0034] Additionally, disclosure of ranges includes disclosure of all values within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.
[0035] Nowadays, various solid electrolytes with high ionic conductivity and good interface contact with electrodes have been developed, which are usually polymer, inorganic and composite electrolytes to improve the cycle performance of batteries. 10 GeP2S 12 Sulfide-based solid electrolytes such as Li6PS5X (X = Cl, Br, I) and Li2S-P2S5 have the highest ionic conductivity (about 10 -2 S cm -1 ), at room temperature, comparable to liquid electrolytes, sulfide all-solid-state lithium batteries are potential alternatives to traditional lithium-ion batteries, which can significantly improve battery energy density and battery safety. In addition, their ductility contributes to the large-scale production of batteries because it avoids high-temperature sintering and improves the processability of the battery's electrolyte and electrodes. However, the realization of high energy density in sulfide-based batteries is challenging due to the difficulty in producing sheet electrodes with high active mass loading. In order to avoid stratification of active materials, conductive agents and solid electrolytes in the positive electrode components and to alleviate the mechanical stress generated during the cycle, the selection of suitable binders and positive electrode active materials is crucial to achieving the cycle performance of sulfide all-solid-state lithium batteries. There is an urgent need for a binder that can alleviate the mechanical stress generated during the positive electrode cycle of solid-state batteries, avoid positive electrode stratification and maintain a high active mass loading of the positive electrode.
[0036] In order to solve the technical problem of poor stability of all-solid-state batteries in the prior art, the present invention proposes a solid-state battery wet-process positive electrode binder prepared from a first polymer material and a second polymer material in a certain ratio. The binder is rich in polar groups and has excellent adhesion, and the interaction between the two polymer materials makes it easily soluble in non-polar solvents and does not damage the sulfide electrolyte. When used in the positive electrode plate, it has a higher ion / electronic conductivity than that of the traditional binder, can broaden the lithium ion transmission channel, and improve the battery cycle performance.
[0037] The technical solution of the present invention is implemented as follows:
[0038] In a first aspect, the present invention provides a composite positive electrode binder for an all-solid-state battery, wherein the composite positive electrode binder comprises a first polymer material and a second polymer material, wherein the molecular weight of the polymer material is 10 4 ~10 6 .
[0039] In one embodiment, the first polymer material includes at least one of poly(ethylene-methacrylate-glycidyl methacrylate), poly(ethylene-glycidyl methacrylate) and polyglycidyl methacrylate.
[0040] In one embodiment, the first polymer material has excellent adhesion, which can greatly alleviate the micro-cracks between the positive electrode and the electrolyte during the charge and discharge process and improve the cycle stability; it also has higher ion / electronic conductivity than traditional binders, can broaden the lithium ion transmission channel, and improve the battery rate performance and cycle characteristics.
[0041] In one embodiment, the second polymer material includes at least one of hydrogenated nitrile rubber (HNBR), nitrile rubber (NBR), ethyl cellulose (EC), styrene butadiene rubber (SBR) and polyvinylidene fluoride (PVDF).
[0042] In one embodiment, the second polymer material interacts with the first polymer material, so that the first polymer material can be better dispersed and dissolved in the solvent.
[0043] In one embodiment, the mass of the first polymer material is set to M, the mass of the second polymer material is set to N, and the M:N is (0.5-2):1;
[0044] In one embodiment, the mass ratio M:N of the first polymer material to the second polymer material can be selected from 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.8:1, 1.9:1, 2:1, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.
[0045] A second aspect of the present invention provides a method for preparing a composite positive electrode binder, the method comprising the following steps:
[0046] S1, adding the first polymer material and the second polymer material into a non-polar solvent for dissolution;
[0047] S2, heating and stirring during dissolution;
[0048] S3, centrifugally drying to obtain a composite positive electrode binder.
[0049] In one embodiment, in the method for preparing the composite positive electrode binder, in step S1, the mass ratio of the first polymer material and the second polymer material to the solvent is 2% to 20%.
[0050] In one embodiment, in the method for preparing the composite positive electrode binder, the mass ratio of the first polymer material and the second polymer material to the non-polar solvent in step S1 can be selected from 2%, 5%, 8%, 10%, 12%, 15%, 18%, 20%, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.
[0051] In one embodiment, in the method for preparing the composite positive electrode binder, the non-polar solvent in step S1 includes at least one of anisole, butyl butyrate, isobutyl isobutyrate, p-xylene and toluene.
[0052] In one embodiment, in the method for preparing the composite positive electrode binder, the dissolution process in step S2 needs to be stirred and heated, the stirring speed is 200 rpm to 600 rpm, the stirring temperature is 40° C. to 80° C., and the stirring is performed until it is completely dissolved.
[0053] In one embodiment, in the method for preparing the composite positive electrode binder, the stirring speed in step S2 can be selected from 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, etc., and the stirring temperature can be selected from 40° C., 50° C., 60° C., 70° C., 80° C., etc. The above numerical ratios are only examples, and the present invention does not impose any limitation thereto.
[0054] In one embodiment, in the preparation method of the composite positive electrode binder, the centrifugal drying in step S3 is centrifuged at a rotation speed of 2000 rpm to 8000 rpm for 5 min to 10 min, and the solid sample is dried at 60° C. to 100° C. for 6 h to 18 h.
[0055] In one embodiment, in the method for preparing the composite positive electrode binder, the centrifugal speed in step S3 can be selected from 2000rpm, 3000rpm, 4000rpm, 5000rpm, 6000rpm, 7000rpm, 8000rpm, etc., the centrifugal time can be selected from 5min, 6min, 7min, 8min, 9min, 10min, etc., the drying temperature can be selected from 60℃, 70℃, 80℃, 90℃, 100℃, etc., and the drying time can be selected from 6h, 8h, 10h, 12h, 14h, 16h, 18h, etc. The above listed numerical ratios are only examples, and the present invention does not impose any limitation on this.
[0056] The third aspect of the present invention provides a positive electrode sheet, comprising the first and second composite positive electrode binders, a conductive agent, a first solid electrolyte and a positive electrode active material.
[0057] In one embodiment, the conductive material refers to one or more of conductive carbon black, conductive graphite, carbon nanotubes, carbon nanofibers, and graphene.
[0058] In one embodiment, the first solid electrolyte material is a sulfide solid electrolyte: Li6PS5X (LPSX, X = Cl, Br, I), Li 10 GeP2S 12 (LGPS) or more; and / or.
[0059] In one embodiment, the positive electrode active material refers to one or more of lithium cobalt oxide (LCO), lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA) and lithium rich manganese-based oxide (LRMO).
[0060] A fourth aspect of the present invention provides a method for preparing a positive electrode sheet, the method comprising the following steps:
[0061] N1. Adding the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder into a solvent;
[0062] N2, stirring, repeating the mixing twice to form a uniform mixed slurry;
[0063] N3, coating the mixed slurry of step N2 on the positive electrode current collector;
[0064] N4, dry;
[0065] N5. After drying, roll pressing and slitting are performed to obtain the positive electrode sheet.
[0066] In one embodiment, in the method for preparing the positive electrode sheet, the mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder in step N1 is: (60-90): (8-38): (1-3): (1-3).
[0067] In one embodiment, in the method for preparing the positive electrode sheet, the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder in step N1 can be selected according to the mass ratio of 60:35:2:3, 65:31:1:3, 70:27:1:2, 75:22:1:2, 80:18:1:1, 85:12:1:2, 90:7:1:2, etc. The above numerical ratios are only examples, and the present invention does not impose any limitation on this.
[0068] In one embodiment, in the method for preparing the positive electrode sheet, in step N1, the solid content of the positive electrode active material, the first solid electrolyte, the conductive agent, and the composite positive electrode binder after mixing with the solvent is 45% to 70%.
[0069] Solid content refers to the percentage of solid components in the composite positive electrode binder.
[0070] In one embodiment, in the method for preparing the positive electrode sheet, the solid content of the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder after mixing with the solvent in step N1 can be selected to be 45%, 50%, 55%, 60%, 65%, 70%, etc. The above values are only examples, and the present invention does not impose any limitation on this.
[0071] In one embodiment, the method for preparing the positive electrode sheet, step N2 is to mix at 1500rpm to 3000rpm for 10min to 60min in a drying room at -60℃ to -30℃ with a high-speed stirrer, then defoam at 500rpm to 1000rpm for 5min to 20min, and repeat the mixing twice to form a uniform mixed slurry.
[0072] In one embodiment, in the method for preparing the positive electrode sheet, the temperature in the drying room in step N2 can be selected to be -60°C, -55°C, -50°C, -45°C, -40°C, -35°C, -30°C, etc., the speed of the high-speed stirrer can be selected to be 1500rpm, 2000rpm, 2500rpm, 3000rpm, etc., the mixing time can be selected to be 10min, 20min, 30min, 40min, 50min, 60min, etc.; the defoaming speed can be selected to be 500rpm, 600rpm, 700rpm, 800rpm, 900rpm, 1000rpm, etc., and the defoaming time can be selected to be 5min, 10min, 15min, 20min, etc. The above values are only examples, and the present invention does not make any limitation to this.
[0073] In one embodiment, in the method for preparing the composite positive electrode sheet, in step N3, the mixed slurry is coated on the positive electrode current collector, and the positive electrode current collector is aluminum foil.
[0074] In one embodiment, in the method for preparing the composite positive electrode sheet, step N4 is drying at 80° C. to 120° C. for 8 h to 16 h, and step N5 is rolling and slitting after drying to obtain the positive electrode sheet.
[0075] In one embodiment, in the method for preparing the composite positive electrode sheet, the drying temperature of step N4 can be selected to be 80°C, 90°C, 100°C, 110°C, 120°C, etc., and the drying time can be selected to be 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, etc. The above values are only examples, and the present invention does not impose any limitation on this.
[0076] The fifth aspect of the present invention provides an all-solid-state battery, comprising the positive electrode sheet, the negative electrode sheet and the second solid electrolyte proposed in the third and fourth aspects.
[0077] The negative electrode sheet preparation method of the present invention comprises the following steps: 95% of negative electrode active material, 2% of solid electrolyte, 2% of conductive agent and 1% of binder are mixed to form negative electrode slurry, the negative electrode slurry is coated on a negative electrode current collector (copper foil), and after drying, the negative electrode sheet is obtained by rolling and cutting. Among the negative electrode active material, graphite: silicon oxygen = 80%: 20%.
[0078] The solid electrolyte layer preparation method of the present invention: the solid electrolyte layer is composed of a second solid electrolyte and a binder; the mass ratio of the two is 99:1.
[0079] In one embodiment, the second solid electrolyte material is a sulfide solid electrolyte: Li6PS5X (LPSX, X = Cl, Br, I), Li 10 GeP2S 12 (LGPS) or more; and / or.
[0080] In one embodiment, the binder material is one or more of polyvinylidene fluoride (PVDF), polyvinyl alcohol (PVA), nitrile rubber (NBR), carboxymethyl cellulose (CMC), polytetrafluoroethylene (PTFE), and polyacrylic acid (PAA).
[0081] The method for preparing an all-solid-state battery of the present invention comprises stacking a positive electrode sheet, a solid electrolyte layer and a negative electrode sheet in sequence and encapsulating them in an aluminum-plastic film. After vacuum is applied to the aluminum-plastic film, the film is sealed and the battery is isostatically pressed at 460 MPa to obtain an all-solid-state lithium-ion battery.
[0082] The embodiments of the present invention will be described in more detail below through examples and comparative examples, wherein all examples and comparative examples are all solid-state battery sample groups prepared by the same process.
[0083] In order to intuitively and comprehensively reflect the advantages of the present invention, all embodiments and comparative examples record or perform the following tests: electronic conductivity, ionic conductivity, 0.1C initial discharge capacity, capacity retention rate after 100 cycles at 0.5C, and capacity retention rate after 100 cycles at 1C.
[0084] It should be noted that the embodiments of the present invention are not limited to these examples.
[0085] The following examples are applications of M:N in all-solid-state batteries at different ratios, wherein M represents poly(ethylene-methacrylate-glycidyl methacrylate) and N represents hydrogenated nitrile rubber.
[0086] Example 1
[0087] 1. Preparation of composite positive electrode binder
[0088] 1) Poly(ethylene methacrylate-glycidyl methacrylate) and hydrogenated nitrile rubber are added into isobutyl isobutyrate solvent at a mass ratio of M:N=1:1 for dissolution.
[0089] 2) The dissolution process requires stirring and heating, with a stirring speed of 350 rpm and a temperature of 80° C. to form a solution with a mass fraction of 8%.
[0090] 3) The solid sample was centrifuged at a rotation speed of 5000 rpm for 7 minutes, and then dried at 80° C. for 12 hours to obtain a composite positive electrode binder.
[0091] 2. Preparation of positive electrode sheet
[0092] 1) The positive electrode active material, solid electrolyte, conductive agent and binder are added into the solvent isobutyl isobutyrate in a mass ratio of 70:27:1:2, and the solid content is 60%.
[0093] 2) Mixing with a high-speed stirrer at 2000 rpm for 30 minutes in a drying room at -50°C, then defoaming at 800 rpm for 10 minutes, repeating the mixing twice to form a uniform mixed slurry.
[0094] 3) Then, the slurry was coated on the positive electrode current collector (aluminum foil) with a scraper in a drying room.
[0095] 4) Transfer to a vacuum oven and dry at 100°C for 12 h.
[0096] 5) After drying, the positive electrode sheet is obtained by roller pressing and slitting.
[0097] 3. Preparation of negative electrode sheet
[0098] 95% of negative electrode active material, 2% of solid electrolyte Li6PS5Cl, 2% of conductive carbon black and 1% of binder PAA are mixed to form negative electrode slurry, which is then coated on the negative electrode current collector (copper foil), dried, rolled and cut to obtain negative electrode sheets. In the negative electrode active material, graphite: silicon oxygen = 80%: 20%.
[0099] 4. Preparation of Solid Electrolyte Layer
[0100] The solid electrolyte layer is composed of a second solid electrolyte Li6PS5Cl and a binder PTFE; the mass ratio of the two is 99:1.
[0101] 5. All-solid-state battery preparation
[0102] The positive electrode, solid electrolyte layer and negative electrode of the battery are stacked and packaged in an aluminum-plastic film in sequence. After vacuum is applied to the aluminum-plastic film, it is sealed and the battery is isostatically pressed at 460 MPa to obtain an all-solid-state lithium-ion battery.
[0103] Example 2
[0104] Example 1 provides a composite positive electrode binder, a positive electrode sheet and a preparation method thereof, and an all-solid-state battery, which are the same as the composite positive electrode binder, positive electrode sheet and preparation method used in Example 1, and the only difference from Example 1 is that in step 1) of the preparation method of the composite positive electrode binder, M:N is 0.5.
[0105] Example 3
[0106] Example 1 provides a composite positive electrode binder, a positive electrode sheet and a preparation method thereof, and an all-solid-state battery, which are the same as the composite positive electrode binder, positive electrode sheet and preparation method used in Example 1, and the only difference from Example 1 is that in step 1) of the preparation method of the composite positive electrode binder, M:N is 0.8.
[0107] Example 4
[0108] Example 1 provides a composite positive electrode binder, a positive electrode sheet and a preparation method thereof, and an all-solid-state battery, which are the same as the composite positive electrode binder, positive electrode sheet and preparation method used in Example 1, and the only difference from Example 1 is that in step 1) of the preparation method of the composite positive electrode binder, M:N is 1.5.
[0109] Example 5
[0110] Example 1 provides a composite positive electrode binder, a positive electrode sheet and a preparation method thereof, and an all-solid-state battery, which are the same as the composite positive electrode binder, positive electrode sheet and preparation method used in Example 1, and the only difference from Example 1 is that in step 1) of the preparation method of the composite positive electrode binder, M:N is 2.
[0111] Comparative Example 1
[0112] The difference between this comparative example and Example 1 is that the composite positive electrode binder prepared in step 1) is replaced by the traditional binder NBR, and the positive electrode is prepared by the traditional binder NBR. The other steps are the same as those in Example 1.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is that poly(ethylene-methacrylate-glycidyl methacrylate) is used instead of the composite positive electrode binder prepared in step 1), and only poly(ethylene-methacrylate-glycidyl methacrylate) is used as the binder to prepare the positive electrode, and the other steps are the same as Example 1.
[0115] Comparative Example 3
[0116] The difference between this comparative example and Example 1 is that hydrogenated nitrile rubber (HNBR) is used instead of the composite positive electrode binder prepared in step 1), and only hydrogenated nitrile rubber (HNBR) is used as a binder to prepare the positive electrode, and the other steps are the same as Example 1.
[0117] Comparative Example 4
[0118] The composite positive electrode binder, positive electrode sheet and preparation method used in Example 1 are the same, and the difference from Example 1 is that in step 1) of the preparation method of the composite positive electrode binder, M:N is 0.05.
[0119] Comparative Example 5
[0120] The composite positive electrode binder, positive electrode sheet and preparation method used in Example 1 are the same, and the difference from Example 1 is that in step 1) of the preparation method of the composite positive electrode binder, M:N is 5.
[0121] The composite positive electrode binders prepared in the above Examples 1 to 5 and Comparative Examples 1 to 5 were used in positive electrode sheets to prepare all-solid-state batteries, and the performance of the all-solid-state batteries was tested. The test results are shown in Table 1 below:
[0122] Electronic conductivity:
[0123] The electronic conductivity of a material is determined by measuring its resistivity. According to the Ampere formula R = U / I, the resistance of the conductor is calculated by measuring the current passing through the conductor and the voltage drop through the conductor, and the geometric dimensions of the sample to be tested are measured, and then the formula Calculate the conductivity.
[0124] Ionic conductivity:
[0125] The AC impedance of the sample is measured, and then the ionic conductivity of the sample is calculated by the formula σ=L / (R×S), where L is the thickness, R is the impedance, and S is the cross-sectional area.
[0126] Cyclic battery capacity retention rate:
[0127] At a temperature of 45°C, charge with a current of 0.5C and 1C respectively to a charging cut-off voltage of 4.2V, switch to constant voltage charging to a cut-off current of 0.05C, stand for 0.5h, then discharge with a current of 0.5C and 1C respectively to a cut-off voltage of 2.5V, stand for 0.5h, enter the next charge and discharge cycle, and so on, for a total of 100 charge and discharge cycles.
[0128] First discharge capacity test:
[0129] At room temperature (25°C), the fully charged battery was discharged at a constant current of 0.1C to a cut-off voltage of 2.5V to obtain the first discharge capacity.
[0130] The performance test results are shown in Table 1.
[0131] Table 1. Performance test results of positive electrode sheets and solid-state batteries
[0132]
[0133]
[0134] According to the above table, it can be seen that: By comparing Examples 1 to 5 with Comparative Examples 1 to 5, the present invention proposes a solid-state battery wet-process positive electrode binder prepared from a first polymer material and a second polymer material in a certain proportion. The first polymer material has excellent adhesion, which can greatly alleviate the micro-cracks between the positive electrode and the electrolyte during the charge and discharge process and improve the battery stability; it also has higher ionic and electronic conductivity than traditional binders, can broaden the lithium ion transmission channel, and improve the battery cycle performance. In addition, the second polymer material and the first polymer material interact with each other, which can better disperse and dissolve the first polymer material in a non-polar solvent; the obtained composite positive electrode binder is rich in polar groups, has excellent adhesion, and will not damage the sulfide electrolyte of the positive electrode material layer. Specifically, the electronic conductivity and ionic conductivity of the prepared positive electrode plate are higher than when using traditional binders. In addition, the capacity retention rate of the all-solid-state battery is higher after 100 cycles.
[0135] In Examples 1 to 5, as the M:N ratio increases, the electronic conductivity, ionic conductivity, capacity retention rate after 100 cycles at 0.5C, and capacity retention rate after 100 cycles at 1C all tend to rise first and then fall, and each battery performance reaches a peak when the M:N ratio is 1:1. Therefore, this composite positive electrode binder can improve the electronic and ionic conductivity of the battery and the battery cycle performance.
[0136] Comparing Example 1 with Comparative Examples 1 to 5, when the traditional binder NBR material is used, the electronic and ion conductivity and battery cycle performance are the worst. Comparative Examples 2 to 3 show that when only poly(ethylene methacrylate-glycidyl methacrylate) and only hydrogenated nitrile rubber (HNBR) are used, the overall battery performance is slightly improved. Comparative Examples 4 to 5 show that when the content of one of the two polymer materials is too little or too much, the overall battery performance will decrease.
[0137] Figure 1 The 0.1C charge-discharge curve in Example 1 shows that the 0.1C first discharge capacity is 210 mAh g -1 .
[0138] It should be pointed out that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A composite positive electrode binder for an all-solid-state battery, characterized in that: The composite positive electrode binder comprises a first polymer material and a second polymer material, wherein the molecular weight of the polymer material is 10 4 ~10 6 .
2. The composite positive electrode binder according to claim 1, wherein the first polymer material comprises at least one of poly(ethylene methacrylate-glycidyl methacrylate), poly(ethylene glycidyl methacrylate) and polyglycidyl methacrylate.
3. The composite positive electrode binder according to claim 1, wherein the second polymer material comprises at least one of hydrogenated nitrile rubber, nitrile rubber, ethyl cellulose, styrene butadiene rubber and polyvinylidene fluoride. 4 . The composite positive electrode binder according to claim 1 , wherein the mass of the first polymer material is set to M, the mass of the second polymer material is set to N, and the M:N is (0.5-2):
1.
5. A method for preparing the composite positive electrode binder according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1, adding the first polymer material and the second polymer material into a non-polar solvent for dissolution; S2, heating and stirring during dissolution; S3, centrifugally drying to obtain a composite positive electrode binder.
6. The method according to claim 5, characterized in that In the step S1, the mass ratio of the first polymer material and the second polymer material to the solvent is 2% to 20%.
7. A positive electrode sheet comprising the composite positive electrode binder according to claims 1 to 7, a conductive agent, a first solid electrolyte and a positive electrode active material.
8. The method for preparing the positive electrode sheet as claimed in claim 7, characterized in that: The steps include: N1. Adding the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder into a solvent; N2, stirring, repeating the mixing twice to form a uniform mixed slurry; N3, coating the mixed slurry of step N2 on the positive electrode current collector; N4, dry; N5. After drying, roll pressing and slitting are performed to obtain the positive electrode sheet.
9. The method according to claim 8, characterized in that The mass ratio of the positive electrode active material, the first solid electrolyte, the conductive agent and the composite positive electrode binder in the step N1 is: (60-90): (8-38): (1-3): (1-3).
10. An all-solid-state battery, comprising the positive electrode sheet, the negative electrode sheet and the second solid electrolyte according to claim 7; The positive electrode sheet is prepared by the method according to claim 8 or 9.
Citation Information
Patent Citations
Glycidyl-containing polymers, polymer compositions comprising them and their use in electrochemical cells
CN112384543A
Preparation method and application of binder for solid-state battery
CN117844403A
Cathode of an all-solid-state lithium-ion battery and all-solid-state lithium-ion battery containing said cathode
US20200152957A1
Solvent for preparing solid electrolyte layer, binder composition comprising same, and solid electrolyte layer, electrode, and all-solid battery formed by using same
US20240079639A1
Cited By
Binder for lithium ion battery as well as preparation method and application of binder
CN120665537A